Comparison of Ibuprofen with Ibuprofen plus Transcutaneous Electrical Nerve stimulation in pain reduction of induced first trimester abortion with misoprostol - Minoo Yaghmaei; Mastaneh Dahi; Mojgan Mokhtari (Mashhad University of Medical Sciences, 2022)
Introduction: Most women who undergo first trimester medical abortion experience abdominal pain and cramps. The present study was performed aimed to evaluate the effect of Transcutaneous Electrical Nerve Stimulation (TENS) on reducing the pain of induction of abortion in the first trimester of pregnancy. Methods: In this single-blind clinical trial which was performed in 2020-2021, for 40 women in the first trimester of pregnancy who were candidate for medical abortion with misoprostol in order to reduce pain, randomly administered Ibuprofen and inactive TENS or Ibuprofen and active TENS with a frequency of 80 Hertz and intensity of 0 to 80 milliampere to reduce pain. These two groups were compared in terms of pain intensity before and after the use of TENS, the amount of used Ibuprofen, satisfaction from the process of medical abortion and complications. Data were analyzed by SPSS (version 16) and Chi-square and Mann-Whitney statistical tests. P<0.05 was considered statistically significant. Results: In the active TENS group, the use of ibuprofen was significantly lower (P= 0.001) and pain reduction was significantly higher (P= 0.001) than the other group. Also in this group, satisfaction with the abortion process was higher (P=0.044). Conclusion: In patients who are hospitalized for medical abortion in the first trimester of pregnancy, in addition to Ibuprofen, TENS can be used for further relief.